Challenges for Fast Radio Bursts as Multimessenger Sources from Binary Neutron Star Mergers - Mohit Bhardwaj; Antonella Palmese; Ignacio Magaña Hernandez; Virginia D’Emilio; Soichiro Morisaki (The Astrophysical Journal)
Fast radio bursts (FRBs) are millisecond-duration transients from extragalactic sources, with their origins remaining a topic of active debate. Among the proposed progenitors, binary neutron star (BNS) mergers are compelling candidates for some nonrepeating FRBs. However, associating FRBs with BNS mergers cannot be based solely on low chance coincidence probability. This study delineates necessary criteria for associating FRBs with BNS mergers, focusing on the postmerger ejecta environment. To underscore the significance of these criteria, we scrutinise the proposed association between GW190425 and FRB 20190425A, considering the requirement for the FRB signal to traverse the dense merger ejecta without significant attenuation to remain detectable at 400 MHz. Our investigation reveals that if the FRB is linked to the gravitational-wave (GW) event, the GW data support a highly off-axis configuration, with a probability of the BNS merger viewing angle p ( θ _v > 30°) being ≈99.99%. This strongly excludes an on-axis system, which is required for this FRB to be detectable. We also find faraway FRB emission models inadequate to explain the FRB 20190425A–GW190425 connection. Thus, we conclude that GW190425 is not related to FRB 20190425A. We discuss the implications for future multimessenger observations, suggesting that BNS merger remnants are unlikely to account for more than 1% of FRB sources. This finding implies that short gamma-ray bursts, which are expected to occur in only a fraction of all BNS mergers, cannot account for the overall characteristics of the FRB host population.